Frequency of predisposing factors for the entry of foreign bodies into the ear, ingestion and aspiration in children under five years in Tabriz, 2019 - Ahmad Shamsi; Leila Valizadeh; Mahni Rahkar Farshi; Mohammad Asghari Jafarabadi (Tehran University of Medical Sciences, 2021)
Background & Aim: Structured description of pediatric medical emergencies requires the assessment and classification of underlying factors. The aim of study was to investigate frequency of predisposing factors for the entry of foreign bodies (FB) in the ear, ingestion and aspiration in children under five years in Tabriz. Methods & Materials: This is a descriptive, cross-sectional study conducted through convenience sampling (n=245) in the ENT and emergency departments and the clinic of childrenchr('39')s hospital in Tabriz, from March 2019 to June 2019. A researcher-made tool including the demographic characteristics form and questionnaire on predisposing factors was used to collect the data. Data was analyzed using the SPSS software version 21 through descriptive statistics. Results: There were 137 (55.9%) cases of  FB aspiration into the airways (upper and lower), and the highest was related to nose. FB in ear was 19.6% and in stomach was 19.2%. Clinical manifestations were pain (50.2%), no clinical signs (29.4%), and the rest were bleeding with pain, cough, shortness of breath, suffocation, wheezing, nausea, and vomiting. The place of event was at home (in living room) and in the evening and night time. FB types included objects, food stuff/snacks/nuts, beans and fruit cores, and toy pieces, and it is most likely to be seed, toy pieces, nuts, shirt buttons, and rosary beads. Conclusion: Parental, child-related, and environmental predisposing factors were reported. Therefore, future studies are suggested to evaluate the contribution of each of three factors and to implement necessary educational, notification, and interventional measures.